ナンキョク タイリク Victoria Valley system ノ ヒョウショクタニ ノ ケイタイ カイセキ ト タニゾコ タイセキブツ ノ アツサ ノ スイテイ - 安仁屋, 政武; アニヤ, マサム; Welch, Roy; Aniya, Masamu (1981)
P(論文) 南極大陸ビクトリア谷系に分布している氷蝕谷の横断形態を, モデル式Z=aX^bを使って解析した。この式で, XとZはそれぞれ谷底中央からの水平距離と高さの座標値で, 1970年に撮影された1 : 60000の空中写真から, 写真測量によって求められた。係数aと指数bは最小2乗法によって決められる。13ヵ所の断面の解析の結果得られた指数bの値は, 1以下から5以上までと幅広く, 値がほぼ2に近いヨーロッパや北アメリカでの結果と異なっている。以上のことから, 指数が1.5～2.0前後の断面と, それ以外の値をもつ断面とでは, 形態が非常に異なっていることが判明した。その解釈として2つの説明, 1)氷蝕の違い, 2)塩風化による斜面発達の過程の違い, が考えられた。谷底堆積物の厚さの推定が行われた。これはモデル式を谷底に外挿して岩床の高度を推定し, 地表面との高度差を算出して得られた。直接検証するデータは無いが, 間接的な方法では, これらの推定値が妥当な範囲にあることが判明した。 The morphology of glacial valleys in the Victoria Valley system, Antarctica, was quantitatively analyzed employing the model Z=aX^b. In this model, the X and Z coordinate values are the distances from and the heights above the valley center as determined by photogrammetric techniques from 1 : 60000 high-altitude aerial photography obtained in 1970. The coefficients "a" and exponents "b" were determined by the method of least squares. Values for the exponents ranged from approximately 0.6 to 5,indicating that the glacial valley cross-sections could be approximated by profiles varying from shallow V's to quintic parabolas. These values differ from those obtained for glacial valleys in Europe and North America, where parabolas with exponents from 1.5 to 2.0 have been found to approximate valley cross-sections. Consequently, it appears that there are distinctive morphological differences among groups of glacial valleys. Two possible explanations for these morphological differences are presented : 1) different modes of glacial erosion; and 2) slopes at different stages of evolution by salt weathering. In addition to morphological factors, estimates of the depth of sediments in the valleys were also attempted by extrapolating the modelgenerated curve beneath the surface deposits to the valley floors. The difference between the photogrammetrically measured surface elevations and the estimated bedrock elevations yielded the depth estimates. Examination of the results indicates that these estimates are reasonably correct when appropriate segments of the valley wall are ...